Regulators of Collagen Fibrillogenesis during Molar Development in the Mouse - Zvackova, Ivana; Matalova, Eva; Lesot, Herve (Frontiers in Physiology, 2017)
Development of mammalian teeth and surrounding tissues includes time–space changes in the extracellular matrix composition and organization. This requires complex control mechanisms to regulate its synthesis and remodeling. Fibril-associated collagens with interrupted triple helices (FACITs) and a group of small leucine-rich proteoglycans (SLRPs) are involved in the regulation of collagen fibrillogenesis. Recently, collagen type XII and collagen type XIV, members of the FACITs family, were found in the peridental mesenchyme contributing to alveolar bone formation. This study was designed to follow temporospatial expression of collagen types XIIa and XIVa in mouse first molar and adjacent tissues from embryonic day 13, when the alveolar bone becomes morphologically apparent around the molar tooth bud, until postnatal day 22, as the posteruption stage. The patterns of decorin, biglycan, and fibromodulin, all members of the SLRPs family and interacting with collagens XIIa and XIVa, were investigated simultaneously. The situation in the tooth was related to what happens in the alveolar bone, and both were compared to the periodontal ligament. The investigation provided a complex localization of the five antigens in soft tissues, the dental pulp, and periodontal ligaments; in the mineralized tissues, predentin/dentin and alveolar bone; and junction between soft and hard tissues. The results illustrated developmentally regulated and tissue-specific changes in the balance of the two FACITs and three SLRPs.